Naltrexone implant treatment for opioid use disorder: analysis of demographic and clinical data - Keskin, Necla; Ege, Funda Çiçek (Journal of Dependence, 2025)
Objective: The aim of this study is to evaluate the demographic and clinical features and outcomes of patients with opioid use disorder who underwent subcutaneous naltrexone implantation. Method: A total of 51 patients with opioid use disorder admitted to Alcohol and Drug Addiction Research, Treatment and Education Center (AMATEM) of Van Training and Research Hospital and treated with naltrexone implant (1000 mg/3 month) were evaluated retrospectively. A data form for demographic and clinical features was filled based on medical records. Results: The mean age of patients was 28.27±7.35 years, age of onset for any drug was 18.69±4.91 and 20.48±4.48 years for opioids. The most used first drug was cannabis followed by heroin. Majority of patients used heroin by smoking and inhalation. The laboratory test results were found to be within normal range. One patient was seropositive for HCV with normal liver function tests. 58.8 % of patients admitted for follow-up at least once in three months and 83.3 % of them maintained to be drug-free as revealed by urine toxicology tests. Local adverse reactions were most reported side effects due to naltrexone implant. Conclusion: Naltrexone implant seems to be an effective and safe treatment choice in opioid use disorder as it increases treatment adherence and rates of drug-free urine samples, and is related with few adverse effects.